Diagnostic performance of clinical characteristics to detect airflow limitation in people living with HIV and in uninfected controls. Issue 10 (30th August 2018) - Ronit, A; Benfield, T; Mocroft, A; Gerstoft, J; Nordestgaard, BG; Vestbo, J; Nielsen, SD; ,
Abstract : Objectives: Chronic obstructive pulmonary disease (COPD) is underdiagnosed in the general population and possibly also in people living with HIV (PLWH). We evaluated the diagnostic performance of symptoms and risk factors for assessment of airflow limitation in PLWH and in uninfected controls. Methods: Spirometry was performed in the Copenhagen Comorbidity in HIV Infection (COCOMO) study and Copenhagen General Population Study (CGPS), and airflow limitation was defined by forced expiratory volume in 1 s/forced vital capacity < lower limit of normal. We calculated the sensitivity, specificity, predictive values and area under the curve (AUC) of symptoms and risk factors for assessment of airflow limitation in PLWH and uninfected controls. Results: A total of 1083 PLWH and 12 074 uninfected controls were included in the study. The sensitivity for sputum, chronic cough, breathlessness, wheezing, current and cumulative smoking and self‐reported COPD was higher, but the specificity lower, in PLWH than in uninfected controls. The negative and positive predictive values were largely similar between the groups. The AUCs were similar or slightly higher in PLWH and highest for > 20 pack‐years smoked [0.65; 95% confidence interval (CI) 0.58–0.72] and wheezing (0.64; 95% CI 0.57–0.71). A summed score for five variables was associated with slightly higher AUC in PLWH compared with uninfected controls [0.71 (95% CI 0.63–0.79) versus 0.65 (95% CI 0.63–0.68), respectively; P = 0.06]. Conclusions: Clinical variables were relatively poor discriminators of airflow limitation in PLWH and uninfected controls. Active COPD case finding by screening for symptoms and relevant exposures, as recommended in the general population, is likely to yield similar diagnostic power in PLWH.